Resisting corporate corruption : cases in practical ethics from Enron through the financial crisis - Arbogast, Stephen V., 1948- 4 0 16; 5 (Hoboken, NJ :;Beverly, MA : John Wiley & Sons, Inc. ;;Scrivener Publishing LLC, 2017)
Resisting Corporate Corruption teaches business ethics in a manner very different from the philosophical and legal frameworks that dominate graduate schools. The book offers twenty-eight case studies and nine essays that cover a full range of business practice, controls and ethics issues. The essays discuss the nature of sound financial controls, root causes of the Financial Crisis, and the evolving nature of whistleblower protections. The cases are framed to instruct students in early identification of ethics problems and how to work such issues within corporate organizations. They also provide would-be whistleblowers with instruction on the challenges they & rsquo;d face, plus information on the legal protections, and outside supports available should they embark on that course. Some of the cases illustrate how & lsquo;The Young are the Most Vulnerable, & rsquo; i.e. short service employees are most at risk of being sacrificed by an unethical firm. Other cases show the ethical dilemmas facing well-known CEOs and the alternatives they can employ to better combine ethical conduct and sound business strategy. Through these case studies, students should emerge with a practical toolkit that better enables them to follow their moral compass. Finally, the cases provide an in depth look at how a corporation becomes progressively corrupted (Enron), how the Financial Crisis was rooted in ethical decay at institutions as diverse as Countrywide, Goldman Sacks, Citigroup, Fannie Mae and Moody & rsquo;s, and at the ethical challenges that persist in the post-Crisis, post-Dodd-Frank environment--;This book teaches business ethics in a manner very different from the philosophical and legal frameworks that dominate graduate schools. The book offers twenty-eight case studies and nine essays that cover a full range of business practice, controls and ethics issues. The essays discuss the nature of sound financial controls, root causes of the Financial Crisis, and the evolving nature of whistleblower protections. The cases are framed to instruct students in early identification of ethics problems and how to work such issues within corporate organizations--
The Enron Cases. Case 1: Enron Oil Trading (A): Untimely Problems in Valhalla -- Essay 1: How to Do an Ethics Case Study -- Case 2: Enron Oil Trading (B): An Opening for Enron Audit? -- Essay 2: How a Corporation Becomes Corrupt -- Case 3: Enter Mark-to-Market: Exit Accounting Integrity? -- Essay 3: Necessary Ammunition: Economic Rationales for Financial Control -- Case 4: Adjusting the Forward Curve in the Backroom -- Case 5: Enron's SPEs: A Vehicle too Far? -- Case 6: Court Date Coming in California? -- Case 7: New Counsel for Andy Fastow -- Case 8: Nowhere to Go with the 'Probability of Ruin' -- Case 9: Lay Back ... and Say What? -- Case 10: Whistleblowing Before Imploding in Accounting Scandals -- Essay 4: Resisting Corporate Corruption: The Enron Legacy -- Essay 5: Underappreciated Origins of the Financial Crisis -- A Personal Memoir -- The Financial Crisis Cases. Case 1: Seeking a Sustainable Business Model at Goldman Sachs -- Case 2: Juggling Public Policy, Politics and Profits at Fannie Mae -- Case 3: Should Countrywide Join the Subprime 'Race to the Bottom'? -- Case 4: Subprime Heading South at Bear Stearns Asset Management -- Case 5: Ratings Integrity vs. Revenues at Moody's Investors Services -- Case 6: Admission of Material Omission? Citigroup's SIVs and Subprime Exposure -- Case 7: Facing Reputational Risk on Goldman's ABACUS 2007-AC1 -- Case 8: Time to Drop the Hammer on AIG's Controls? -- Case 9: Write to Rubin? -- Pressure on Underwriting Standards at Citigroup -- Case 10: Lehman Brothers Repo 105 -- Essay 6: Wall Street and the Crisis -- Causes, Contributions and Problems to Fix -- The Post-Crisis Cases -- Reforms, Resistance, Continuing Realities. Case 1: Morgan Stanley Seeks a Sustainable Business Model after the Financial Crisis -- Case 2: Back to the Future on Goldman Sachs Reputational Risk -- Case 3: 'Take Customer Cash to Survive?' Compliance and Chaos at MF Global -- Case 4: Fix the LIBOR Fix? -- Case 5: Too Big to Know What's Going on at Banamex? -- Case 6: Take CitiMortgage to the Feds? -- Case 7: Chipping Away at Dodd-Frank's Volcker Rule? -- Essay 7: 'And the Young Shall be Thrown Under the Bus' -- Lessons in Resisting Unethical Conduct from Enron Through the Financial Crisis -- Essay 8: Resisting Corporate Corruption, 2017 -- Improved Conditions, Unresolved Issues -- A Note on Blogs and Law Firms -- A Note on Sources -- Index -- The Financial Crisis Cases -- The Post-Financial Crisis Cases.
Revised edition of the author's Resisting corporate corruption, [2013].
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 10, 2017).
John Wiley and Sons
Keywords: 2 -- 0; Case studies. -- Corrupt practices -- Enron Corp;Enron Corp. -- 6; 2008-2009; Moral and ethical aspects. -- Business ethics.;Industrial management;Global Financial Crisis, 2008-2009 -- 20 -- Case studies; 20; Case studies.;Electronic books